The Law of Anime: Otaku, Copyright, Fair Use, and It’s Infringements in Indonesia - Akhmad Al-Farouqi; Nandang Sutrisno; Budi Agus Riswandi (Fakultas Hukum Universitas Islam Indonesia, 2020)
The massively growing popularity of Japanese animation or Anime creates a certain movement and has exported cultural form in another reflection from their fans in many countries. It can be in a form of data such as films, pictures, videos, or made by fans such as fan-subs, fan arts, fan-fictions or it can be in a real form such as clothes, merchandises or costumes for cosplayers. In Indonesia copyright is regulated in the Law no. 28 of 2014 on Copyright while internationally copyright are regulated by some of international convention and agreements such as Trade-Related Aspects of Intellectual Property Rights Plus concluded by WTO; Paris Convention for the Protection of Industrial Property, the Berne Convention for the Protection of Literary and Artistic Works, and the Rome Convention concerning protection of neighboring rights to literary works which are concluded by WIPO. Even though the infringement of intellectual property rights violated copyright and it is nationally and internationally protected by law, but the phenomenon of violation of this anime is can be easily found in daily life and massively growing, and due to unclear limitations and parameters of the balance in enjoying the economic benefits of reasonable interest which also regulated in Article 44 and is called as fair use however, questions arise, what kinds of movement which infringing the law and which one is not.